De casa para outras casas: trajetórias socioespaciais de trabalhadoras domésticas residentes em Aparecida de Goiânia e trabalhadoras em Goiânia - LOPES, Renata Batista (2008)
The origin of female domestic labor in Brazil is linked to the slavery period, in this way; it is marked by racial bias. Despite the remote origin, domestic workers as workers remain stigmatized marginally included in society and the world of work. Negative social representations relating to the origin and nature of the occupation (work servile, degrading, naturalized women, disqualified, "service in black", etc.). Have always been part of the collective imagination and the social life of women, who perform this function, it was expressed covertly in various locations and social situations. For this it is essential question: How social representations on women, and poor domestic worker, crystallized in the social imaginary collective (society sexist, racist and class) influence on the various dimensions of life of this group of women, whether in social, affective, professional ,...? And yet: What are the ties they establish with the local daily basis by which they move? In particular regarding the establishment of the place - "the extent appropriate space and lived through the body? The guiding lines of study are the categories gender, race, corporality, domestic workers, social representations, trajectories sociogeographic, segregation / exclusion and place. Considering the above, the purpose of this study is to analyze the phenomenon of segregation / exclusion socio in view of domestic workers who work and live in Goiânia in the city of Aparecida de Goiânia, trying to identify their sociogeographic trajectories - "Spacely differential" - and understand that the bonds they establish with the local women who attend, and the main elements in the establishment of such ties. The path opened by the Human Geography in the 1970s, with the introduction of new issues on the production of space by mankind, required expansion and diversification of its theoretical and methodological until the "new geographies" current, neglected geographies in fact, taken and informal look at the scientific tradition, that in the contemporary beginning to gain visibility, which this work aims to contribute. The search (multi / trans / inter) disciplinary approach to quality, flexible and multi methodological, had the contribution of workers who daily move from their homes to the workplace whose life stories were recorded by means of semi-structured individual interviews recorded. The content of the interviews sought to seize the items "subjective" account for the displacements and corporality of workers, that is, their condition of poor women, domestic workers, black or white.